2016
DOI: 10.1016/j.jpainsymman.2015.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Shock Index and Decreased Level of Consciousness as Terminal Cancer Patients' Survival Time Predictors: A Retrospective Cohort Study

Abstract: An SI ≥ 1.0 along with DLOC is a highly reliable tool for predicting short-term survival time in terminal cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…20,21 In a retrospective cohort study of patients with advanced cancer, the combination of SI ≥ 1.0 and a decreased level of consciousness was identified as a useful assessment tool for short-term survival times. 13 SI was demonstrated to be a sensitive indicator of left ventricular dysfunction, and a persistently high SI suggests an unstable hemodynamic state in critically ill patients. 25 An increase in SI at the onset of a markedly reduced oral intake in noncancer patients indicates an unstable hemodynamic state.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…20,21 In a retrospective cohort study of patients with advanced cancer, the combination of SI ≥ 1.0 and a decreased level of consciousness was identified as a useful assessment tool for short-term survival times. 13 SI was demonstrated to be a sensitive indicator of left ventricular dysfunction, and a persistently high SI suggests an unstable hemodynamic state in critically ill patients. 25 An increase in SI at the onset of a markedly reduced oral intake in noncancer patients indicates an unstable hemodynamic state.…”
Section: Discussionmentioning
confidence: 99%
“…We also converted systolic blood pressure and pulse to SI. Based on previous studies, SI was classified into 3 categories.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Low oxygen saturation has been reported to be a risk factor for death in patients with advanced cancer [1][2][3][16][17][18]. Randomized controlled trials have shown that long-term oxygen for patients with chronic obstructive pulmonary disease with severe hypoxemia resulted in reduced mortality [19,20].…”
Section: Introductionmentioning
confidence: 99%